Energy spectra of the fibonacci graphene superlattice - Korol, Anatoliy; Isai, Valeriy (My University, 2013)
Energy spectra of the graphene-based Fibonacci superlattice (SL) in the presence of the forbidden band in graphene have been investigated.
Keywords: graphen; Fibonacci; spectre; графен; спектр; Фібоначчі; Фибоначчи; кафедра фізики та професійної безпеки